2018
DOI: 10.1111/jopr.12965
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Torque of Variable‐Thread Tapered Implants in the Posterior Maxilla: A Clinical Study

Abstract: ITVs of variable-thread implants were significantly influenced by variations in bone quality and implant position in the posterior maxilla. Despite the influence of bone quality on primary stability, the mean ITVs attained with variable-thread tapered implants in poor bone quality were within the recommended range for immediate loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
2
1
1
Order By: Relevance
“…The IT values reported here ranging from 13 to 22 N cm were much lower than the clinically recommended torque value of 35 N cm [ 24 26 ]. The lower torque values can be explained by our use of artificial bone, mimicking type-4 bone, and a cylindrical non-self-tapping design limiting the interface between thread and bone.…”
Section: Discussioncontrasting
confidence: 60%
“…The IT values reported here ranging from 13 to 22 N cm were much lower than the clinically recommended torque value of 35 N cm [ 24 26 ]. The lower torque values can be explained by our use of artificial bone, mimicking type-4 bone, and a cylindrical non-self-tapping design limiting the interface between thread and bone.…”
Section: Discussioncontrasting
confidence: 60%
“…Regarding immediate provisionalization, while most reports indicate that this procedure has similar esthetic results when compared to conventional loading protocols [42], it is paramount to recognize the technical challenge of this approach as well as the importance of the implant design. In this study, the implant had a tapered geometry, which enables implant placement between adjacent natural teeth [6], provides high primary stability [43][44][45][46], and improves esthetics by allowing a gradual expansion of the alveolar ridge [7]. Furthermore, the implant-abutment connection was conical, which is known to be tight and mechanically stable, and provides a built-in platform shift that has been shown to reduce inflammation and bone loss in peri-implant tissues [10] as well as to support favorable esthetic results [47].…”
Section: Discussionmentioning
confidence: 99%
“…RFA analysis is the most accepted method for evaluating implant stability [ 26 29 ]. RT value is another marker for evaluating stability [ 30 ]. Tabassum et al reported a correlation between RFA and RT values [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%